Respostas
respondido por:
3
Calcule :
a) (-3)^7 : (-3)² = DIVISÃO de BASES iguais CONSERVA a base
e subtrai o expoente
(-3)⁷ : (-3)² =
(-3)⁷⁻² =
(-3)⁵ ( resposta)
b) [ (-4)² ]³ =
(-4)²ˣ³ =
(-4)⁶ ( resposta)
c) ( 2x y²)³ =
(2xy²)³ observe
2³x³y²ˣ³
2³x³y⁶ = 8x³y⁶ ( resposta)
a) (-3)^7 : (-3)² = DIVISÃO de BASES iguais CONSERVA a base
e subtrai o expoente
(-3)⁷ : (-3)² =
(-3)⁷⁻² =
(-3)⁵ ( resposta)
b) [ (-4)² ]³ =
(-4)²ˣ³ =
(-4)⁶ ( resposta)
c) ( 2x y²)³ =
(2xy²)³ observe
2³x³y²ˣ³
2³x³y⁶ = 8x³y⁶ ( resposta)
biacris2:
muito obrigado ... pode chamar no chat ?
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás